4 - The Kamajoi Militia: Civil War, Internal Displacement and the Politics of Counter-Insurgency*: by Patrick K. Muana - Patrick K. Muana (Africa Development, 1997)
The reckless massacre, mass displacement, starvation and wanton pillaging following the invasion of Kailahun District, Sierra Leone, by the Revolutionary United Front (RUF/SL) in 1991 and the failure of the National Provisional Ruling Council (NPRC), after overthrowing the All Peoples Congress (APC) regime, to end the reign of terror, eventually galvanized the civilian population into effective resistance of both the RUF and the increasingly demoralized and undisciplined national army. Refugee camps situated around the safe urban enclaves of Bo, Kenema and Makeni, which had been inundated by internally displaced civilians, organized self-defence militias, which became the counterinsurgency forces. The most important of these militias, which has been deployed in all the contested conflict zones, is the Kamajoi (or Kamasoi), a Mende word which literally means 'a past master at doing mysterious things'. The author examines the failure of the RUF to maintain mass civilian support for the movement, the formation of the Kamajoi militia, its controversial status as a parallel defence institution, and issues surrounding its future role in nascent democratic politics in Sierra Leone.